2011
DOI: 10.1007/s10661-011-2247-8
|View full text |Cite|
|
Sign up to set email alerts
|

Monitoring of heavy metals uptake and allocation in Pinus sylvestris organs in alkalised soil

Abstract: The concentration of heavy metals in soil and in Scots pine (Pinus sylvestris) organs growing on a pH gradient from 4.0 to 7.9 of soil at different distances from a cement plant was monitored. Emission for over 40 years of alkaline dust (pH 12.3-12.6) into the atmosphere in North Estonia had resulted in alkalisation and elevated concentration of total heavy metals in upper layers of the soil (0-30 cm), which was considerable even 10 years after the dust pollution stopped. Monitoring showed that the accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 28 publications
4
15
0
Order By: Relevance
“…Wahsha et al (2012) found that plant concentrations of Cu, Pb, Zn, and Fe were higher, and Cr and Ni were similar to the results of our study. Finally, Cr, Pb, and Fe were lower, Zn was higher, and Cu similar to observations by Ots and Mandre (2012).…”
Section: Resultssupporting
confidence: 85%
“…Wahsha et al (2012) found that plant concentrations of Cu, Pb, Zn, and Fe were higher, and Cr and Ni were similar to the results of our study. Finally, Cr, Pb, and Fe were lower, Zn was higher, and Cu similar to observations by Ots and Mandre (2012).…”
Section: Resultssupporting
confidence: 85%
“…However, the accumulation of elements in plant tissues is a dynamic and complex process, which is conjugated with other biochemical and metabolic processes occurring in the plant (Giertych et al, 1997). The transport of elements within plant tissues and their translocation and concentration in different organs are influenced significantly by many factors including environmental conditions (e.g., soil pH and other edaphic properties, pollution level) (Giertych et al, 1997;Ots and Mandre, 2012) and processes intrinsic to the plant, like the selective removal and exchange of nutrients from xylem sap (Finér and Kaunisto, 2000;Monoshima and Bondietti, 1990), mobility and solubility of elements and competition by the same carrier sites in absorption mechanisms (Ots and Mandre, 2012), and synergetic or antagonistic interactions between elements (Kabata-Pendias, 2011).…”
Section: Uranium Accumulation Trend In Plantsmentioning
confidence: 99%
“…Other authors focused their attention on heavy metals accumulation by higher plants in order to study the urban pollution [17-20]. …”
Section: Introductionmentioning
confidence: 99%